2014
DOI: 10.1080/13102818.2014.947725
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community development of biofilm in Amaranth decolourization technology analysed by FISH

Abstract: The aim of this study was to elucidate the role, the space distribution and the relationships of the bacteria from the genus Pseudomonas in a biofilm community during semi-continuous Amaranth decolourization process in model sand biofilters. The examined parameters of the process were as follows: technological parameters; key enzyme activities (azoreductase, succinate dehydrogenase, catechol-1,2-dioxygenase, catechol-2,3-dioxygenase); the number of azo-degrading bacteria and the bacteria from genus Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Reaching the critical concentration of the pollutants in the landfill leachate was related to the raised concentration of pollutants fed into the reactor and to the adsorption and absorption of toxic pollutants in the flocs and their subsequent accumulation. We registered similar effects in other processes with activated sludge at the entry of dyes, fuel oil, nitrophenols, chlorophenols, and others into treatment plants [32,54,56,57]. These accumulated contaminants in the flocs of the sludge can also be seen in the photos (Figure 7).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Reaching the critical concentration of the pollutants in the landfill leachate was related to the raised concentration of pollutants fed into the reactor and to the adsorption and absorption of toxic pollutants in the flocs and their subsequent accumulation. We registered similar effects in other processes with activated sludge at the entry of dyes, fuel oil, nitrophenols, chlorophenols, and others into treatment plants [32,54,56,57]. These accumulated contaminants in the flocs of the sludge can also be seen in the photos (Figure 7).…”
Section: Discussionsupporting
confidence: 61%
“…External calibration by multi-element standard solution was performed. The concentrations of the elements were determined using the isotopes as follows: macroelements ( 27 Al, 136, 138 Ba, 42,44 Ca, 54,57 Fe, 39 K, 24,25,26 Mg, 55 Mn, 23 Na, 31 P and 28 Si) and the micro-and trace elements ( 107,109 Ag, 75 As, 209 Bi, 110,112,114 Cd, 59 Co, 52 Cr, 133 Cs, 63,65 Cu, 200 Hg, 139 La, 96,98 Mo, 60,62 Ni, 204,208 Pb, 85,87 Rb, 121,123 Sb, 77,78 Se, 118,120 Sn, 86,88 Sr, 46,48 Ti, 232 Th, 238 U, 51 V and 64,66 Zn). The simultaneous determination of all elements in the samples was achieved by reducing the signal of the macroelements thanks to the application of a dynamic bandpass tuning parameter RPa, as described in Lyubomirova [37].…”
Section: Chemical and Technological Analyzesmentioning
confidence: 99%
“…The most important of them, as being able to participate in both the xenobiotics biodegradation and the denitrification, are the bacteria in the genus Pseudomonas. In our previous studies their key role in the detoxification of different pollutants had been demonstrated [49][50][51]. Details related to the importance of their spatial arrangement and the unculturable part of the group had been elucidated [49,51].…”
Section: Resultsmentioning
confidence: 99%
“…They have better resistance to fluctuations in loads, starvation periods, and washouts (Chandran and Das, 2011). In the previous investigation (Belouhova et al, 2014), the bacteria from genus Pseudomonas played an important role in the adaptation of biofilms for the biodegradation of azo dyes. This study focused on increasing the potential of tested isolates to generate stable bonding with the abiotic surface in the form of a biofilm (Rajendran et al, 2015).…”
Section: Identification Of Bacterial Speciesmentioning
confidence: 97%
“…The phylogenetic dendograms of the isolates are shown in Figure 1. The ability to produce biofilm of tested isolates using adherence assay A biofilm is an assemblage of microbial cells that are irreversibly associated (not removed by gentle rinsing) with a surface and enclosed in a matrix of primarily polysaccharide material (Belouhova et al, 2014). Microorganisms attach to surfaces and develop biofilms, and biofilm-associated cells can be distinguished from their suspended counterparts because of their generation of an extracellular polymeric substance (EPS) matrix, reduced growth rates, and the up-and down-regulation of specific genes (Cerron et al, 2015).…”
Section: Identification Of Bacterial Speciesmentioning
confidence: 99%